Critical role of Frizzled1 in age‐related alterations of Wnt/β‐catenin signal in myogenic cells during differentiation. (29th January 2014) - Doi, Ryosuke; Endo, Mitsuharu; Yamakoshi, Kimi; Yamanashi, Yuji; Nishita, Michiru; Fukada, So‐ichiro; Minami, Yasuhiro
<x xml:space="preserve">Abstract</x> Activation of Wnt/β‐catenin signal in muscle satellite cells (mSCs) of aged mice during myogenic differentiation has been appreciated as an important age‐related feature of the skeletal muscles, resulting in impairment of their regenerative ability following muscle injury. However, it remains elusive about molecules involved in this age‐related alteration of Wnt/β‐catenin signal in myogenic cells. To clarify this issue, we carried out expression analyses of Wnt receptor genes using real‐time RT‐PCR in mSCs isolated from the skeletal muscles of young and aged mice. Here, we show that expression of Frizzled1 (Fzd1) was detected at high levels in mSCs of aged mice. Higher expression levels of Fzd1 were also detected in mSC‐derived myogenic cells from aged mice and associated with activation of Wnt/β‐catenin signal during their myogenic differentiation in vitro. We also provide evidence that suppressed expression of Fzd1 in myogenic cells from aged mice results in a significant increase in myogenic differentiation, and its forced expression in those from young mice results in its drastic inhibition. These findings indicate the critical role of Fzd1 in altered myogenic differentiation associated with aging.